2020
DOI: 10.1371/journal.pone.0236807
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, diversity and persistence of Listeria monocytogenes in swine slaughterhouses and their association with food and human listeriosis strains

Abstract: Listeria monocytogenes is the etiological agent of listeriosis, a major foodborne disease and an important public health concern. Contamination of meat with L. monocytogenes occurs frequently at the slaughterhouse. Our aims were; 1) to investigate the distribution of L. monocytogenes in the processing areas of four swine slaughterhouses; 2) to describe the diversity of L. monocytogenes strains by pulsed-field gel electrophoresis; 3) to identify persistent L. monocytogenes strains and describe their distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
(101 reference statements)
0
15
0
1
Order By: Relevance
“…Many studies reported the presence of L. monocytogenes resistant to QACs in different food processing facilities [ 65 , 124 , 194 , 195 ]. Several have also linked QAC resistance to persistence of L. monocytogenes in food production environments [ 65 , 195 , 196 , 197 ].…”
Section: Biocide Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported the presence of L. monocytogenes resistant to QACs in different food processing facilities [ 65 , 124 , 194 , 195 ]. Several have also linked QAC resistance to persistence of L. monocytogenes in food production environments [ 65 , 195 , 196 , 197 ].…”
Section: Biocide Susceptibilitymentioning
confidence: 99%
“…Many studies reported the presence of L. monocytogenes resistant to QACs in different food processing facilities [ 65 , 124 , 194 , 195 ]. Several have also linked QAC resistance to persistence of L. monocytogenes in food production environments [ 65 , 195 , 196 , 197 ]. BC resistance in L. monocytogenes is considered low-level and is unlikely to lead to resistance to the concentrations of these compounds usually applied in the food industry (generally 200–1000 mg L −1 ) [ 70 , 194 ].…”
Section: Biocide Susceptibilitymentioning
confidence: 99%
“…monocytogenes is frequently isolated in various food products. This pathogen results in listeriosis, which remarkably affects pregnant women, newborns, and individuals with immunodeficiency (10,11). Due to the ability of this microorganism to growth at low temperatures (2-4 • C), there is a particular concern about the presence of L. monocytogenes in meat and poultry products (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Four biofilm-forming strains of L. monocytogenes were used in the present study, LM 2A51, LM C97, LM 3C15, and LM 3C24. These strains were isolated from the floor of different areas in the pork slaughterhouses after sanitation procedures ( Table 1 ) and belong to the serotypes 1/2a, 1/2a, 1/2a, and 1/2b, respectively, and they were characterized by Pulsed Field Gel Electrophoresis (PFGE) and are referred to the following PFGE types LS4, LS19, LS21, and LS16, respectively, in Cherifi et al (2020) . Five coagulase-negative staphylococci (CNS) of bovine origin were used to generate cell-free supernatants with an anti-biofilm activity ( Goetz et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%